Low-fat and low-protein diets are associated with hearing discomfort among the elderly of Korea. Issue 10 (21st September 2015) - Kim, So Young; Sim, Songyong; Kim, Hyung-Jong; Choi, Hyo Geun
Abstract: Research on the effect of low-fat intake on hearing is limited. This study aimed to elucidate the relationship between fat, carbohydrate and protein intake and the presence of hearing discomfort among the elderly. The Korean National Health and Nutrition Examination Survey was conducted from 2009 through to 2012. A total of 4615 participants ranging in age from 60 to 80 years underwent a pure-tone audiometric evaluation, a physical examination and a nutritional survey. The associations between the participants' hearing thresholds and their protein/fat/carbohydrate intake/total energy intake were analysed using simple and multiple regression models with complex sampling adjusted for confounding factors, such as BMI, income level, smoking status and a history of hypertension, hyperlipidaemia and diabetes. Low fat and protein intakes were associated with hearing discomfort (OR 0·82, 95 % CI 0·71, 0·96, P =0·011; OR 0·81, 95 % CI 0·67, 0·96, P =0·017, respectively). This study revealed that low fat and protein intakes are associated with hearing discomfort in the elderly Korean population.